2012
DOI: 10.4028/www.scientific.net/amm.212-213.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grass Coverage on the Sediment Concentration in Overland Flow in the Hillslope-Gully Side Erosion System

Abstract: By scouring experiments, the changeable process and characteristics of sediment concentration in sloping surface with different coverage degrees and spatial locations of grass were studied. Five grass coverage degrees of 0, 30%, 50%, 70%, 90%, three spatial locations of grass (upslope, mid-slope, low-slope) and two water inflow rates of 3.2L/min, 5.2L/min were applied to a 0.5 by 8 m soil bed in scouring experiments. Results showed that in the hillslope–gully side erosion system, the grass coverage has great e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Fr was subcritical flow on the 5 • slope. This result agrees with Pan and Shangguan [39], Li et al [40], and Zhang and Hu [17], who all indicated that the flow regime of overland flow on sloped grass plots was laminar. In contrast, as slope gradient increased, the flow regime of overland flow shifted from laminar and subcritical flow to laminar and supercritical flow, suggesting that in our study slope gradient had a greater influence on flow regime than vegetation cover.…”
Section: Effects Of Vegetation Cover and Slope Gradient On Runoff Hydsupporting
confidence: 90%
“…Fr was subcritical flow on the 5 • slope. This result agrees with Pan and Shangguan [39], Li et al [40], and Zhang and Hu [17], who all indicated that the flow regime of overland flow on sloped grass plots was laminar. In contrast, as slope gradient increased, the flow regime of overland flow shifted from laminar and subcritical flow to laminar and supercritical flow, suggesting that in our study slope gradient had a greater influence on flow regime than vegetation cover.…”
Section: Effects Of Vegetation Cover and Slope Gradient On Runoff Hydsupporting
confidence: 90%
“…where Vu i is the ratio of all the vegetation control area in the time zone i; ∆A Vcontrol,i is the total area of vegetation in time zone i (m 2 ); Veg is vegetation coverage (%); f (Veg) is function of Veg, it refers to runoff or sediment retention rate of the forestland or grassland with certain vegetation coverage, and f (Veg) is the average value of runoff or sediment retention rates in the time zone i. Most flume test researches in the Loess Plateau lack the complete information about the runoff and sediment retention rate of grassland and forestland with different cover [73][74][75][76]. Xiong et al [77] systematically deconstructed the experimental data from different slope runoff plots in the Loess Plateau, and summarized benefit indices of runoff and sediment reduction by forestland and grassland of different qualities in years with different runoff and sediment levels [77], as shown in Table 3.…”
Section: Consideration Of Vegetation Units In the Time-area Methodsmentioning
confidence: 99%